Does anxiety cause angina recurrence after percutaneous coronary intervention in patients with STEMI? - Zhang, Zhipeng; Wei, Xing; Wei, Jing; Wang, Yuhui; Luo, Chunmiao (Frontiers in Cardiovascular Medicine, 2023)
Background Statistics show that approximately 70% of patients with acute ST-segment elevation myocardial infarction (STEMI) experience relief from chest pain symptoms within 48 h post-percutaneous coronary intervention (PCI). However, over 30% of these patients still suffer from angina post-PCI during their hospital stay and after discharge. Although the interrelation between cardiovascular diseases and psychological states, notably anxiety and stress, has been extensively studied and acknowledged, the specific influence of anxiety disorders on post-PCI clinical outcomes for STEMI patients, especially the recurrence of angina, remains undefined. Methods This study included a total of 324 STEMI patients who underwent PCI treatment due to chest pain in our hospital. Baseline and surgical data for all patients were collected. During their hospital stay, patients’ emotional states were assessed using the Hamilton Anxiety Scale, while angina was evaluated using the Seattle Angina Questionnaire. All patients were followed up for 6 months post-discharge to gather clinical data and outcomes, analyzing whether anxiety disorders would affect the recurrence of angina post-PCI in STEMI patients. Results Out of the 324 patients, 82 experienced recurrent angina symptoms within 6 months post-PCI discharge. Compared to the non-recurrence group, the recurrence group showed statistically significant differences in anxiety levels. Other differing factors included the spouse's health status, cardiac Killip classification, severity of coronary lesions, and the state of the coronary microcirculation. After utilizing propensity score matching to eliminate inherent biases between the two groups at a 1:1 ratio, the COX regression analysis indicated that a patient's anxiety status is a risk factor for the occurrence of angina post-PCI in STEMI patients (HR = 2.094, 95% CI = 1.248–3.514, P = 0.005). Conclusion Anxiety is a significant factor for short-term recurrence of angina post-PCI in STEMI patients. This further confirms the crucial impact of mental health on cardiovascular wellness.